2023
DOI: 10.1002/btm2.10603
|View full text |Cite
|
Sign up to set email alerts
|

Mechanochemical coupling of MGF mediates periodontal regeneration

Ying Zhao,
Songbai Zhang,
Bo Cheng
et al.

Abstract: Clinical evidence shows that the mechanical stimulation obtained from occlusion could enhance periodontal ligament (PDL) remodeling. Mechano‐growth factor (MGF) is a growth factor produced specifically following mechanical stimulus Here, we aim to investigate the mechanical enhancement potential and mechanism of the MGF in PDL regeneration. In vivo study found that MGF produced from the PDL under occlusion force could strongly enhance PDL remodeling. In vitro experiments and mathematical modeling further confi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2025
2025

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 66 publications
0
1
0
Order By: Relevance
“…(2) MAPK is a protein kinase family and a key signaling pathway through which mechanical signals promote cell apoptosis via phosphorylation cascades involving ERK, p38, and JNK. In fibroblasts in the periodontal ligament, activation of the p38/MAPK pathway by mechanical stress has been widely reported ( 62 ). Zhu et al first reported the involvement of the p38/MAPK pathway in mechanotransduction in hUSLFs in the context of POP development ( 43 , 63 ).…”
Section: Impact Of Biomechanical-biochemical Coupling On Fibroblast F...mentioning
confidence: 99%
“…(2) MAPK is a protein kinase family and a key signaling pathway through which mechanical signals promote cell apoptosis via phosphorylation cascades involving ERK, p38, and JNK. In fibroblasts in the periodontal ligament, activation of the p38/MAPK pathway by mechanical stress has been widely reported ( 62 ). Zhu et al first reported the involvement of the p38/MAPK pathway in mechanotransduction in hUSLFs in the context of POP development ( 43 , 63 ).…”
Section: Impact Of Biomechanical-biochemical Coupling On Fibroblast F...mentioning
confidence: 99%